2021
DOI: 10.1093/bjc/azab009
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from Relative Deprivation to Individual Violence: The Effect of Subjective Perception and Emotional Resentment in South Korea

Abstract: Criminological studies assert that individuals’ psychological cognition and emotional resentment mediate the effect of economic deprivation on individual violence; however, a limited number of studies have empirically addressed these subjective mediations. Furthermore, the effect of relative deprivation in Asian counties is seldom investigated. To fill this gap, we construct theoretical path models and examine the argument of relative deprivation in South Korea. A total of 2,040 individuals are surveyed face t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…This study examined the impact of relative deprivation on college students’ aggressive behavior and its underlying mechanisms. The results showed that relative deprivation could positively predict college students’ aggressive behavior, which was consistent with previous research conclusions [ 22 , 54 56 ]. It can be seen that relative deprivation, a social environmental factor, is an important predictor of aggressive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…This study examined the impact of relative deprivation on college students’ aggressive behavior and its underlying mechanisms. The results showed that relative deprivation could positively predict college students’ aggressive behavior, which was consistent with previous research conclusions [ 22 , 54 56 ]. It can be seen that relative deprivation, a social environmental factor, is an important predictor of aggressive behavior.…”
Section: Discussionsupporting
confidence: 92%